Neta C. Crawford: Argument and Change in World Politics. Ethics, Decolonization, and Humanitarian Intervention. - Alena Drieschová (Czech Journal of International Relations, 2005)
Neta C. Crawford: Argument and Change in World Politics. Ethics, Decolonization, and Humanitarian Intervention. Cambridge Studies in International Relations. 1st ed. Cambridge: Cambridge University Press, 2002, 15 + 466 stran, ISBN 0-521-00279-6 (signatura knihovny ÚMV 50 060).